Japanese Netizens’ Expressive Speech Acts’ Expression Realm towards Prime Minister Shinzo Abe's Resignation - Timur astami (Lingua Cultura, 2021)
The aim of the research was to find out the respondent’s form, approach, and purpose in expressing speech acts in online media. As a public space, the media is a place where its readers are allowed to freely express their expression, and the comment section is one of the public spaces of the media. The research applied a library research method of collecting data from several online media sources. There were 10 data collected to know the netizen’s opinion about Prime Minister Abe’s resignation. With the SBLC technique, where the research observed without engaging in the conversations, the data would be collected, categorized, and chosen based on the purpose of the expressive speech. The data result in the respondents’ negative and positive expressive speeches on Prime Minister Abe’s resignation. Meanwhile, the respondents take direct approaches to express thanks, satire, suspicion, criticism, insult, disappointment, and censure.